Development and Testing of Long-Lasting IRS Products While Revising the WHO Test Protocol - Skovmand, Ole; Ongmayeb, Gisele; Kounbobr Dabiré, Roch; Namountougou, Moussa; Georges Meda, Benson; Trang, Trung; Dang, Duoc; Nguyen, Tuan (Journal of Public Health International, 2021)
The paper describes the development of a long-lasting product for Intra-domicile residual spray (IRS) and shows it is possible to obtain a residual effect of nearly 2 years. However, to obtain that the methods currently recommended by WHO for laboratory evaluation had to be modified and approached methods closer to the semi-field and field evaluations as applied in later phases of WHO procedures. Surfaces with high pH resulted in short residual effect unless the formulations were mixed with a silicone coating. Screening in huts constructed for the purpose was realised by dividing the wall surfaces in 25 test plots of 0.5 m² where formulations were applied randomly with more repeats the closer to the final formulation. Mud and concrete surface were more challenging than wood surface and stones and these could be dropped for screening. Wall surfaces heated by sun were repellent to non-blood fed mosquitoes, and the test in huts were limited to the mornings. However, blood fed mosquitoes were not repelled. Cone tests on mud-walls are complicated by the uneven structure of the surface and a better way of attaching cones to avoid mortality errors was developed. Formulations that can be applied and last for two mosquito seasons produce big cost savings for IRS programs, since program costs are mostly application costs.
Keywords: Intra-domicile residual spray IRS; Long Lasting IRS; Evaluation of WHO test method; Carbamates; Organophosphorus insecticides OPs.